ANALYSIS OF SPEAKING ASSESSMENT IN ESP SPEAKING CLASS - Ardiyansah, Tri Yuli (Jetlal, 2019)
English for Specific Purposes has grown to become one of the most prominent areas of EFL teaching. ESP provides learning of English skills such as: Speaking, Listening, Reading, and Writing. There are also assessment used in ESP for those four skills. In speaking skill, the instruction of the assessment should be given by the instructors based on the objectives of speaking skill itself. In developing speaking test, the instructors should consider on some aspects such as general objective of the test, specific objective of the test, the type of the test, time allotment and how to score the test. This research used qualitative research because the focuses of this research were to explain the assessment process implied by the instructors and to find the kind of assessment type, material, source and scoring used by the instructors in ESP Speaking Class at University of Muhammadiyah Malang. In this research, the writer used Observation, Interview, and Documents as the research instruments. The result of this research showed that the instructors used most of assessment types based on basic types of speaking assessment (Intensive, Responsive, Interactive, and Extensive) excluding (Imitative). The material and source sometimes can vary depending on the each objective of the syllabus. And in the scoring method, the instructors used analytic and holistic scoring.